Perancangan dan Implementasi Smart Brooding System untuk Kandang Ayam Broiler Berbasis Arduino Nano - Sanhaji, Ganis; Ihsan, Muhammad; Sumantri, Cyndi Odilia; Nareswari, Natasya; Suherman, Rizky Herdyan (Jurnal Sains dan Teknologi (JSIT), 2025)
Broiler chicken farming is one of the important livelihoods in Indonesia which is generally carried out traditionally.Problems often experienced by broiler chicken farmers are the temperature and humidity conditions that are not idealduring the brooding period, which is one of the important factors in increasing broiler chicken production. The purpose ofthis study is to control and monitor the temperature and humidity in broiler chicken coops during the brooding period. Tocontrol and monitor the temperature and humidity, a device was designed for use in chicken coops. The device uses anArduino Nano as a microcontroller, a DHT22 sensor, and a PWM dimmer module as a temperature and humidityregulator, and an I2C LCD as a display for temperature and humidity values. The results of sensor readings on thedesigned device will be compared with sensor readings on a standard tool that has been calibrated daily for 21 days.Controlling the temperature and humidity of broiler chicken coops with an automatic system has proven effective, with anaverage measurement error of 0.65% temperature and 4.48% humidity, so that the cage environment remains in optimalconditions for chicken growth. The results showed that cage A (closed house with automatic control) produced a higheraverage chicken weight of 967.9 grams compared to cages B and C. Overall, stable temperature, humidity, cagecleanliness, and feed and vitamin management were the main factors determining the success of broiler chicken farming.